Potential and strategies for developing agate-based creative tourism (BIS Humanities and Social Science, 2026)
Agate stones constitute an important component of Indonesia’s cultural heritage, valued for their historical significance, symbolic meanings, and aesthetic qualities. In recent years, however, their popularity has declined due to shifting market trends and the weakening of traditional jewelry industries. This study aims to (1) examine the potential of agate as a creative tourism attraction and (2) formulate development strategies for agate-based tourism rooted in traditional jewelry craftsmanship in Pasirjambu. A qualitative case study approach was employed involving agate artisan communities. Data were collected through participant observation, in-depth interviews (n = 4 artisans representing four generational groups), and limited visitor surveys, and were analyzed using SWOT to systematically map internal and external development factors. The findings indicate that agate demonstrates strong potential within creative tourism frameworks, particularly through educational tourism, experiential tourism, and shopping-based tourism. Visitors show interest not only in finished jewelry products but also in production processes, direct artisan interaction, and hands-on workshop experiences. Strategic priorities include strengthening destination branding, diversifying creative tourism products, optimizing digital marketing, and reinforcing Hexa Helix collaboration among artisans, local government, and tourism stakeholders. A community-based development approach is essential to ensure long-term sustainability and improve artisan welfare. This study contributes an operational model for creative industry–based tourism that is adaptable to regions with similar cultural and material resources and supports the revitalization of Indonesia’s traditional agate sector.